2005
DOI: 10.1038/sj.onc.1209124
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the cytokinesis regulator ECT2 at G2/M phase stimulates association of the mitotic kinase Plk1 and accumulation of GTP-bound RhoA

Abstract: The epithelial cell transforming gene 2 (ECT2) protooncogene encodes a Rho exchange factor, and regulates cytokinesis. ECT2 is phosphorylated in G2/M phases, but its role in the biological function is not known. Here we show that two mitotic kinases, Cdk1 and polo-like kinase 1 (Plk1), phosphorylate ECT2 in vitro. We identified an in vitro Cdk1 phosphorylation site (T412) in ECT2, which comprises a consensus phosphospecific-binding module for the Plk1 polo-box domain (PBD). Endogenous ECT2 in mitotic cells str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 29 publications
3
120
0
Order By: Relevance
“…This augmentation remains unexplained; although it is possible that the over accumulation of p105HEF1 might result in increased phosphorylation. Alternatively, there are examples of proteins in which a single residue is the target of different kinases [41,42]. So we can not exclude that other kinase(s) phosphorylate HEF1 on ser-369 but also on another residue leading to an HEF1 isoform that would be less sensitive to degradation and would be part of the p115 band.…”
Section: Discussionmentioning
confidence: 97%
“…This augmentation remains unexplained; although it is possible that the over accumulation of p105HEF1 might result in increased phosphorylation. Alternatively, there are examples of proteins in which a single residue is the target of different kinases [41,42]. So we can not exclude that other kinase(s) phosphorylate HEF1 on ser-369 but also on another residue leading to an HEF1 isoform that would be less sensitive to degradation and would be part of the p115 band.…”
Section: Discussionmentioning
confidence: 97%
“…Second, we asked whether phosphorylation of Ataxin-10 by the Plk1-kinase domain was essential for Ataxin-10 to interact with Plk1-PBD, since other Plk1 substrates involved in cytokinesis are also found to interact with Plk1 PBD, e.g., Ect2 19 and …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Given that Ect2 is an excellent Plk1 substrate, 30 it is possible that Plk1 phosphorylation triggers a conformational change in Ect2 that induces its central spindle relocalization. Alternatively, Plk1 may phosphorylate Ect2's binding partner CYK-4, creating a docking site for the N-terminal BRCA1 C-terminus (BRCT) domain of Ect2, a potential phosphopeptide-recognition motif.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicated that such forced exit is accompanied by violent blebbing of the plasma membrane, an actomyosin-and RhoA-dependent process that resembles ectopic furrow formation. 30 Interestingly, whereas control cells blebbed violently, bleb formation was suppressed in Plk1-depleted and BI 2536-treated cells. Thus, cortical contractility that ensues after Cdk1 inactivation appears to require Plk1 activity, consistent with the observed defects in activation of the Ect2-RhoA network and cytokinesis initiation in BI 2536-treated cells.…”
Section: A Role For Plk1 In Cytokinesis Initiationmentioning
confidence: 99%